Expression of Ki-67 and E-cadherin in patients with non-small cell lung cancer attending a tertiary care hospital (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Background: E-cadherin and Ki-67 expressions may provide real-time insights into the tumor's status and can be utilized as targeted therapeutics for lung cancer. We aimed to explore the expression of Ki-67 and E-cadherin in non-small cell lung cancer (NSCLC) patients and to identify their association with clinicopathological features.Methods: In this cross-sectional study, forty formalin-fixed paraffin-embedded (FFPE) NSCLC tissue blocks were identified from January to October 2022, based on hospital records from the Department of Pathology of National Institute of Diseases of the Chest and Hospital, Dhaka Medical College and Hospital. Samples were reevaluated for tissue quality, diagnosis, and exclusion-inclusion criteria. Finally, twenty-five samples were analyzed, and relevant clinicopathological data were collected from patients or authorized representatives. Ki-67 and E-cadherin expression were analyzed by immunohistochemistry and their relationships with each other.Results: Ki-67 expression was positive in 40% of the NSCLC tissue, and E-cadherin was negative in 40% of the NSCLC tissue. No statistically significant relation was found between the expressions of Ki-67 and E-cadherin. No statistically significant association was found in Ki-67 and E-cadherin expressions with clinicopathological characteristics except E-cadherin with comorbidity.Conclusion: Positive expression of Ki-67 and negative expression of E-cadherin was found in two-fifths of NSCLC tissues but not significant. Simultaneous estimated of Ki-67 and E-cadherin may contribute to the treatment planning and predict prognosis of the NSCLC patients.